Development of an assessment guide to evaluate meaningful outcomes for people living with dementia who are engaged in reablement programs. Issue 20 (25th September 2022) - O'Connor, Claire M. C.; Rowlands, Allison; Poulos, Christopher J.
Abstract: Purpose: Clinical practice guidelines for dementia recommend the provision of rehabilitative or reablement interventions that support functioning. This project sought to develop an assessment guide, centring on goal attainment scaling (GAS), for practitioners to measure attainment of meaningful outcomes for people living with dementia participating in reablement programs. Materials and methods: To assist in guide development, two focus groups (people impacted by dementia [ n  = 10]) explored priority reablement goals. Two further focus groups (allied health practitioners [ n  = 11]) explored understanding and experience using GAS, opinions on what goals would be realistic, and how an assessment guide could best support practice. Results: The key focus group themes that emerged and which underpinned guide development were: 'what is possible'; 'who sets the goals'; 'practitioner perspectives on using GAS'. Leisure was a key goal priority for people impacted by dementia, and echoed by practitioners. The assessment guide is structured around three steps: choosing goals (using focus group derived Reablement Goal Lists ); defining goals (using a new Dementia-specific SMART Framework ) ; scoring goals (using GAS-Light ). Conclusions: Providing a structured approach to evaluation of reablement programs for people living with dementia could lead to more consistent service provision, improved outcomes and opportunities for benchmarking. Implications for Rehabilitation: Dementia is a leading cause of disability in older people. Rehabilitative interventions such as reablement are recommended to support functioning in people living with dementia, but there is currently no consistent method of selecting and evaluating attainment of meaningful outcomes. This study describes the reablement goals identified by people impacted by dementia as being most important, along with allied health practitioner views on goal-setting and the use of Goal Attainment Scaling (GAS). Study findings were used to develop a structured assessment guide employing three steps: choosing reablement goals; defining those goals using a new dementia-specific SMART Framework; and scoring goals using GAS-Light. A consistent approach to goal selection and evaluation of attainment for people impacted by dementia participating in reablement programs may lead to more effective rehabilitative interventions in this group.